The association between pathological internet use and comorbid psychopathology: a systematic review - Carli, Vladimir; Durkee, T.; Wasserman, Danuta; Hadlaczky, G.; Despalins, R.; Kramarz, E.; Wasserman, Camilla; Sarchiapone, Marco; Hoven, Christina W.; Brunner, Romuald; Kaess, Michael (Psychopathology, 2013)
BACKGROUND: Pathological Internet use (PIU) has been conceptualized as an impulse-control disorder that shares characteristics with behavioral addiction. Research has indicated a potential link between PIU and psychopathology; however, the significance of the correlation remains ambiguous. The primary objective of this systematic review was to identify and evaluate studies performed on the correlation between PIU and comorbid psychopathology; the secondary aims were to map the geographical distribution of studies, present a current synthesis of the evidence, and assess the quality of available research. - SAMPLING AND METHODS: An electronic literature search was conducted using the following databases: MEDLINE, PsycARTICLES, PsychINFO, Global Health, and Web of Science. PIU and known synonyms were included in the search. Data were extracted based on PIU and psychopathology, including depression, anxiety, symptoms of attention deficit and hyperactivity disorder (ADHD), obsessive-compulsive symptoms, social phobia and hostility/aggression. Effect sizes for the correlations observed were identified from either the respective publication or calculated using Cohen's d or R(2). The potential effect of publication bias was assessed using a funnel plot model and evaluated by Egger's test based on a linear regression. - RESULTS: The majority of research was conducted in Asia and comprised cross-sectional designs. Only one prospective study was identified. Twenty articles met the preset inclusion and exclusion criteria; 75% reported significant correlations of PIU with depression, 57% with anxiety, 100% with symptoms of ADHD, 60% with obsessive-compulsive symptoms, and 66% with hostility/aggression. No study reported associations between PIU and social phobia. The majority of studies reported a higher rate of PIU among males than females. The relative risks ranged from an OR of 1.02 to an OR of 11.66. The strongest correlations were observed between PIU and depression; the weakest was hostility/aggression. - CONCLUSIONS: Depression and symptoms of ADHD appeared to have the most significant and consistent correlation with PIU. Associations were reported to be higher among males in all age groups. Limitations included heterogeneity in the definition and diagnosis of PIU. More studies with prospective designs in Western countries are critically needed.
Published online: July 31, 2012
Gesehen am 10.03.2021